Internal audit functioning problems in the public sector - Khorguashvili, Tea; Khorguashvili, Natia ("Intercultural Dialogues" Transactions, 2023)
In order to ensure internal financial control of the state, the need to have an internal audit structure, the stages of formation and development at the legislative level are discussed in the paper. The essence, types, purpose and tasks of the internal audit, at the self-level stage of the implementation of the internal financial control of the state, because the introduction of the system and in general, the proper functioning of the internal audit is an actual challenge for our country not only in terms of fulfilling its obligations to the European Union, but it is not a tool that provides a democratic state Development or public sector work efficiently and effectively.